Carbon Dioxide Triggers Carbon Nanotube Nucleation: Isotope Labeling Study on the Growth Process of Individual Nanotubes. (1st July 2022) - Ishimaru, Ryoya; Otsuka, Keigo; Inoue, Taiki; Chiashi, Shohei; Maruyama, Shigeo
Abstract : Growing long and high-density arrays of semiconducting single-walled carbon nanotubes is the key to building high-performance electronics. From the growth process perspective, the density and length of carbon nanotubes are determined by their nucleation probability from individual catalysts, subsequent growth rates, and growth lifetime. Here, we study the effects of additive oxygen-containing species on the growth process at the individual nanotube level during alcohol chemical vapor deposition. When tracing the growth process by isotope labeling techniques, the growth rates are slowed down upon the addition of CO2 due to carbon removal from catalysts. This simultaneously leads to a noticeable extension of the growth lifetime, which has the overall effect of lengthening the nanotube arrays. According to the relationship between the timing of CO2 supply and the growth initiation time of each nanotube, we surprisingly find that the oxidants also trigger the growth initiation, leading to the improvement of nanotube density. As all these effects of the additive oxidants can be explained by the tuning of the supersaturation level of carbon on catalysts, our results suggest the importance of choosing the appropriate balance of carbon sources and oxidants for the simultaneous control of density and length of carbon nanotube arrays.